2023
DOI: 10.3390/en16041597
|View full text |Cite
|
Sign up to set email alerts
|

A New Two-Foci V-Trough Concentrator for Small-Scale Linear Fresnel Reflectors

Abstract: We present the design of an original secondary cavity for use in Small-Scale Fresnel Reflectors in photovoltaic applications. The cavity is similar to the classical V-trough, but the primary reflector system is configured so that there are two focal points on the aperture. The rays coming from each side of the primary system reach the opposite side of the cavity, producing a non-symmetrical distribution of the irradiance. This modifies the acceptance half-angle and allows us to break the maximum limit for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(70 reference statements)
0
0
0
Order By: Relevance
“…Oprea et al [42] indicated that the optical efficiency could be estimated by a function of two parameters: the ray acceptance rate and the average number of reflections, n. The role this average n plays when calculating the irradiance losses is briefly recalled: in general [37], the fraction of the radiation incident on the aperture that is transmitted to the absorber needs to be multiplied by ρ n m , where ρ m is the reflectivity of the mirror. Pardellas et al [27] indicated that slight errors in the calculation of n are almost irrelevant to the final value of ρ n m (this is also verified herein).…”
Section: The Main Elements Of a Concentratorsupporting
confidence: 83%
See 1 more Smart Citation
“…Oprea et al [42] indicated that the optical efficiency could be estimated by a function of two parameters: the ray acceptance rate and the average number of reflections, n. The role this average n plays when calculating the irradiance losses is briefly recalled: in general [37], the fraction of the radiation incident on the aperture that is transmitted to the absorber needs to be multiplied by ρ n m , where ρ m is the reflectivity of the mirror. Pardellas et al [27] indicated that slight errors in the calculation of n are almost irrelevant to the final value of ρ n m (this is also verified herein).…”
Section: The Main Elements Of a Concentratorsupporting
confidence: 83%
“…A standard V-cavity was used in the design of a daylighting system based on optical fiber bundles and a small-scale linear Fresnel reflector [26]. Concentrated photovoltaic systems based on a small-scale Fresnel reflector have also used the standard V-trough cavity [27]. All these studies used a standard V-trough cavity.…”
Section: Introductionmentioning
confidence: 99%